Estimation of Reservoir Rock Formation and Hood Stone in Manifestation Area of Tulehu Salahutu Healer - Ambon Island Based on Magnetic Survey - Jufri Jufri; Sunaryo Sunaryo; Adi Susilo (Natural B, Journal of Health and Environmental Sciences, 2015)
The magnetic survey has been done in the area of geothermal manifestations Tulehu, Salahutu, Central Maluku in Ambon Island which has high temperature reservoir. The aim of this research was to know the formations reservoir and cap rock in the area of geothermal manifestations Tulehu. The measurement of data is done using magnetometer PPM type G-856, in the area of around the hot springs Hatuasa Tulehu broadly of 1.78 km x 1.25 km, which consists of 238 measuring points with spacing 50 m. Data processing to begin with IGRF correction, diurnal correction, flat surface reduction, upward continuation and reduction to the pole. Interpretation was based on three cross - section models: slice AB, BC, and DE. The modeling of the results indicates the presence of caprock formations suspected as alluvial (Qa) with susceptibility contrast 0.0102 SI to 0.0416 SI, whereas the reservoir rocks formation is suspected rocks of volcanic Ambon (Tpav) had been around demagnetization with susceptibility contrast 0.0001 SI, in the deepness of 1850 m to 2775 m the surface below.